2020
DOI: 10.1155/2020/9672093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Osteoarticular Extracorporeal Irradiated Autograft for Malignant Bone Tumor

Abstract: Background and Objectives. Osteoarticular extracorporeal irradiated autograft is an alternative operation technique to prosthetic devices or allografts for reconstruction after resection of bone malignancies. The aim of this study is to assess the complications, radiographic changes, and functional outcomes of osteoarticular ECIA. Methods. We retrospectively reviewed 33 patients who underwent osteoarticular ECIA after bone tumor resection from 1988 to 2014. We investigated complications, radiographic changes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Though there are various reconstruction techniques described which aim to provide a stable and functional elbow, there is a lack of consensus regarding the method of choice. Anatomical reconstructions like the use of osteo-articular graft and recycled tumor bone seem to provide good initial function but are associated with availability issues and higher delayed complication (2,22). Non-anatomical reconstruction like radial transposition to humeral trochlea, though durable are plagued with restricted function (3,5,7,9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there are various reconstruction techniques described which aim to provide a stable and functional elbow, there is a lack of consensus regarding the method of choice. Anatomical reconstructions like the use of osteo-articular graft and recycled tumor bone seem to provide good initial function but are associated with availability issues and higher delayed complication (2,22). Non-anatomical reconstruction like radial transposition to humeral trochlea, though durable are plagued with restricted function (3,5,7,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Both these options require a unique infrastructure for graft processing and are associated with complications like osteotomy healing, wound healing issues, graft resorption, late graft fractures and instability (4,6,22). These techniques may not be suitable in cases that require adjuvant radiation for adequate oncological control.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al [ 36 ] reported no infections in their series of nine patients with type 2 periacetabular resections who were reconstructed with ECI-recycled autograft and endoprosthetic replacement. Takenaka et al [ 37 ] found a significantly high rate of complications in their series of 33 patients but their cohort consisted of autografts from various locations, like proximal humerus, proximal tibia, scapula, and only three acetabula. We believe, as they also stated in their paper, that the high heterogeneity in autograft location, method of fixation, and tumor type which also necessitated chemotherapy might have influenced the incidence and type of complications in their series.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation consists of 60–70 Gy in a single dose [ 88 , 90 ]. A limitation of this procedure is that the irradiated bone fragments have no blood supply and this can lead to infections, fractures, non-union, and bone re-absorption [ 90 , 91 ]. To avoid this problem, a vascularized bone graft can be associated with the irradiated bone fragment, improving reconstruction and increasing vascularization [ 4 , 89 , 90 ].…”
Section: Reconstruction Using Biological Materialsmentioning
confidence: 99%